Hall measurement method for the detection of material defects in plastic-embedded permanent magnets of rotors - Brela, Matthäus; Michalski, Markus; Gebhardt, Hans Joerg; Franke, Jörg (IECON Proceedings (Industrial Electronics Conference), 2013)
The efficiency of electric drives is determined by the mechanical and magnetic properties of the functional elements, such as stator and rotor. Due to the electromagnetic interaction with the magnetic field, generated by the stator, the rotor transforms the magnetic energy into a rotational motion. It is characterized by its magnetization, its magnetic field strength, the field distribution and its geometric dimensions. The current challenge is to produce electrical drives with minimal loss. This requires ensuring the magnetic characteristics of the rotors. Errors that can occur during manufacture are cracks, blowholes or inclusions in the permanent magnet. Those can lead to commutation problems or to increased noise. For this purpose, a non-destructive and non-contact measurement method, based on the measurement of the magnetic field with Hall-effect sensors to detect defects in plastic-bonded permanent magnet rotors was developed. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuators and System Integration; Diagnostic and Prognostic; Fault Detection; Permanent Magnet Machines; Sensors